Precoding Design for Two-Cell MIMO-NOMA Uplink With CoMP Reception - Wang, Hong; Leung, Shu-Hung; Song, Rongfang (IEEE communications letters, 2018)
An optimization framework for the precoder design of two-cell multiple-input multiple-output non-orthogonal multiple access (NOMA) uplink with a co-ordinated multipoint reception and orthogonal space-time block coding is formulated. A precoding scheme with closed-form beamforming and corresponding computationally efficient iterative power allocation (PA) design is proposed to minimize the total transmit power subject to signal-to-interference-plus-noise ratio constraints. It is shown that the proposed NOMA scheme outperforms the NOMA with equal PA and orthogonal multiple access schemes because of its increased diversity and optimized PA.